Identification of stress and symptoms present in mastectomized women - Pricilla Cândido Alves; Camila Félix Américo; Ana Fátima Carvalho Fernandes; Violante Augusta Batista Braga (Rev Rene)
This study aimed to go into the occurrence of stress and to describe the associated symptomatology in mastectomized women through the application of the Inventory of Symptoms of Stress for Adults of Lipp (ISSL). This transversal research, was carried in June 2009, with 14 women belonging to the Group of Mastectomized Women, from Fortaleza-Ce, Brazil. The symptoms experimented in the week before the meeting and that dominated the stress in a phase of resistance were the most common. And the stress was observed in six women. It was concluded that the structural changes in the breasts are a source of stress and should be recognized and worked by health professionals, especially by the nursing team in the daily contact with this group, in order to build self-knowledge strategies of acceptance of the modified body.